Complex Fuzzy MARCOS and WASPAS Approaches with Z-Numbers for Augmented Reality Decision Making - Shahid, Aliha; Ashraf, Shahzaib; Chohan, Muhammad Shakir (Spectrum of Operational Research, 2026)
This study introduces two innovative decision-making methods, MARCOS and WASPAS, based on complex fuzzy Z-number sets. The methodology employs these approaches to evaluate the application of augmented reality (AR) in contemporary society as a case study, highlighting their advantages and nuanced differences. The complex fuzzy Z-number, which integrates Z-number and complex fuzzy set theories, serves as the foundation of this research. The study presents comprehensive flowcharts for both MARCOS and WASPAS, detailing their decision-making processes. A thorough analysis of the results is provided, along with future research directions that emphasize the potential of this methodological framework. The findings contribute to advancing decision-making in AR applications by offering comparative insights using complex fuzzy Z-number sets. Furthermore, the comparison section demonstrates the methodological robustness and validity of the proposed approach.